THE DEVELOPMENT OF MUSICAL HEARING IN SOLFEGGIO TEACHING THROUGH A MULTIMODAL TREATMENT OF ATONAL AND EXTENDED-TONAL MUSIC BY SERBIAN COMPOSERS - Beočanin, Jelena; Kaplarević, Marija (Teme, 2024)
The subject of this paper is the development of musical hearing of university students through solfeggio learning, in which selected passages from the extended-tonal and atonal music of Serbian composers are treated multimodally (by activating several sensory modalities). The development of musical hearing was carried out through the process of literal parallelism in the perception and performance of extended-tonal and atonal music of Serbian composers. The research method is a pedagogical experiment in parallel groups – the testing technique was applied. The aim of the research is to examine the influence of literal parallelism in auditory perception and performance on improving musical hearing in third-year university students. The authors conclude that the application of literal parallelism in auditory perception and performance in third-year students’ solfeggio instructions only partially contributed to the development of hearing. We believe that the reasons for this result lie in the limitations of the applied experimental research – the experimental program itself was conducted in classes for only half an hour on a weekly basis. Also, an appropriate sample of students is, although common for smaller faculties such as art ones, too small to draw general conclusions. With all of the above in mind, the authors believe that the application of literal parallelism should be introduced during earlier levels of education, as they are indispensable for working on the complex content of extended-tonal and atonal music.